Recent advances in two-dimensional MXenes for power and smart energy systems. (June 2022) - Thakur, Nikhil; Kumar, Pawan; Sati, Dinesh C.; Neffati, R.; Sharma, Pankaj
Abstract: Batteries and supercapacitors have emerged as potential candidates from the category of energy storage technologies to address the energy demand. With a detailed search, the advancement of innovative two-dimensional materials introduces a new revolution in energy storage systems. MXene, a new category of flexible 2-D materials is becoming more popular for energy storage systems. MXene has improved the quality of supercapacitors. Furthermore, MXene has assisted batteries in achieving large capacity while providing quick charge-discharge due to its appropriate interlayer spacing as well as distinctive chemistry. Such accomplishments are the consequence of MXene's intrinsic characteristics including excellent electrical conductivity, as well as the potential to sustain modifications, adapting the electrodes to a particular purpose. Furthermore, MXene has proven its worth by allowing supercapacitors or even batteries to move away from convention and explore into the region of Micro-Supercapacitors (MSCs), batteries, etc. other than lithium-ion. Here, in this present review we discuss the current state of energy storage systems based on the MXene's and after that we discuss about the structure and applications. In the last section, we discuss about the challenges and future scopes of MXene's. Highlights: MXene, flexible 2-D materials for energy storage systems are reviewed. Structure and synthesis methods are presented. Properties of MXene's particularly Mechanical, Electronic and Magnetic are described. Applications of MXenes are discussed in respect of batteries, supercapacitors, etc. Some other applications, viz. antennas, biosensor, are also incorporated briefly.